Correlation of Ambient Temperature with Increasing of Covid19 Cases in a Tropical City - Putri Nilam Sari; Azyyati Ridha Alfian; Fea Firdani (Universitas Airlangga, 2021)
Introduction: On March 26, 2020, the government confirmed the first positive case of Covid19 in Padang City. This condition continues increasing, although several policies were created in preventing the spread of Covid19 . The geographical location of Padang City, which is close to the equator, causes the ambient temperature to be very optimum. It needs to be examined from the ambient temperature indicator, which is considered correlated with the spread of the coronavirus. Methods: This study used an ecological design. Spearman rank correlation test was carried out between daily temperature and daily cases due to Covid19 in one year to determine their correlation and test for time lag 0, 7, 14, and 21 according to coronavirus incubation. The cases of Covid19 data were obtained from the Padang City Health Office daily report, and the ambient temperature data were obtained from the Meteorology, Climatology and Geophysics Agency, Teluk Bayur Maritime Meteorology Station, Padang City. Results and Discussion: This study proves a significant negative correlation between minimum temperature (20.7°C - 26.5°C) with daily cases in all-time lags and average temperature (24.4°C - 29.3°C) with a daily case in time lag 7, 14, and 21. This range becomes a suitable temperature to reduce the transmission of Covid19 in Padang city. Conclusion: The optimum ambient temperature in the equatorial region is a factor in slowing the incubation of the coronavirus. Nevertheless, strict implementation of health protocols and efforts to trace contacts with positive Covid19 patients are still needed to prevent coronavirus transmission between humans.